Prototype of a Counseling Gamification Model based on Pappaseng Values: Social Learning Theory Approach to Overcome Academic Dishonesty - Meilsyah Cahyamadani; Verawati ITM; Fatimah Khairunnisa; Akid Saputra Alam; Muhammad Ilham Bakhtiar; M. Amirullah (International Journal of Multicultural Counseling and Development, 2026)
Academic dishonesty remains a problem in schools, showing that knowledge alone is not enough to shape adolescent character. Positive attitudes and behaviors, especially academic honesty, must also be developed. This study examines the application of gamification in classical guidance and counseling services based on Pappaseng values using a Social Learning Theory approach to address academic dishonesty among adolescents. Using the ADDIE method, limited to the analysis, design, and development stages, the study reviewed relevant national and international journals on gamification, guidance and counseling services, Pappaseng values, and Social Learning Theory. The findings show that gamification increases student engagement through challenges, choices, and feedback. Pappaseng strengthens contextual moral values, especially honesty and responsibility. Social Learning Theory supports behavior change through observation, imitation, and reinforcement from the social environment.